Ethanol affects behavior and HPA axis activity during development in zebrafish larvae - Wenxiao Du (Nature Portfolio, 2020)
Abstract Recent studies have shown that long-term alcohol intake from food can lead to numerous mental disorders in humans, and the social and health effects of excessive intake of alcohol currently represent serious problems for governments and families worldwide. However, to date, it has not been determined how alcohol affects the hypothalamic–pituitary–adrenal (HPA) axis. The zebrafish offers a good model for studying the toxicology of food-grade ethanol. In the present study, using zebrafish larvae exposed to 1% ethanol, we performed zebrafish behavioral analysis. Samples were collected for enzyme-linked immunosorbent assay (ELISA) and quantitative real time-polymerase chain reaction (qRT-PCR) experiments, and statistical analysis was performed. We found that ethanol decreased the locomotor activity of zebrafish larvae, which showed a more intense reaction to external stimuli. Ethanol also increased the level of HPA axis hormones in zebrafish larvae, influenced the level of neurotransmitters, and altered the expression of key genes in neurotransmitter metabolism. Ethanol exposure affects zebrafish behavior, increases the level of HPA axis hormones in zebrafish larvae, affects the level of neurotransmitters, and affects the expression of key genes in dopamine and serotonin metabolism. These findings may help to elucidate the effects of ethanol on HPA axis activity.